Enhancing emotional intelligence through sleep therapy in high-stress professionals: a case-control study on efficacy and predictive factors - Zhai, Yujia; Ji, Weiqiang; Li, Yugui; Du, Qingfeng (Frontiers in Psychiatry, 2025)
BackgroundSleep disturbances can significantly impair emotional intelligence (EI), particularly among professionals in high-stress occupations. This study evaluated the effectiveness of sleep therapy (ST) in enhancing EI and identified key predictors of therapeutic success.MethodsWe conducted a retrospective analysis of 471 adults from high-stress professions who completed a 12-week intervention at Bengbu Third People’s Hospital. Among them, 214 received psychoeducational treatment and 257 underwent sleep therapy. A case-control study was performed on the 257 sleep therapy patients. Pre- and post-treatment assessments measured EI components, sleep quality, psychological status, and physical health. Patients were stratified into high and low EI groups based on post-treatment EIS scores. Univariate and multivariate logistic regression analyses identified predictors of EIS improvement.ResultsFollowing the 12-week intervention, the ST group showed significantly greater improvement in total EIS score (60.87 vs. 58.39, P<0.001) compared to a psychoeducational therapy group. Multivariate analysis identified ST intervention (P<0.001) and higher adherence (P = 0.002) as significant protective factors for EI, whereas increasing age was a risk factor (P = 0.001). Compared to the low EI group, the high EI group demonstrated significantly better baseline adherence (70.7% vs. 52.6% full adherence, P = 0.010), greater sleep improvement (ΔPSQI: 3.2 vs. 1.9, P<0.001), lower anxiety (SAS: 46.6 vs. 49.2, P = 0.006), and higher self-esteem (SES: 31.8 vs. 30.4, P<0.001).ConclusionSleep therapy effectively enhances EI in high-stress professionals suffering from sleep disorders. Treatment efficacy is strongly influenced by adherence, baseline psychological and physical health status, and sleep quality improvements.